Studi Komparatif Nikah Siri Dalam Perspektif Hukum Islam Dan Hukum Positif Di Indonesia - Noviana, Titik; Slamet, Slamet; Viviyanti Johar, Intan; Sayidatu Zahrok, Firlia; nida, khairun (LPPM UNU BLITAR, 2025)
if it meets the pillars and requirements of marriage, but is not recognized legally by the state because it is not formally registered. This creates serious issues in legal protection for women and children, and creates inequalities in family rights. This study aims to comparatively analyze how Islamic law and positive law in Indonesia view the practice of siri marriage, as well as to examine its social and legal implications in society. This research uses a library research method with a descriptive-comparative approach and a normative legal analysis of relevant literature and regulations. Research findings indicate that Islamic law emphasizes the validity of marriage according to Shari'ah through the fulfillment of the pillars and conditions of marriage, while Indonesian positive law requires the registration of marriage to ensure legal strength and protection of civil rights. The practice of unregistered marriage often disadvantages women in terms of maintenance rights, divorce, and inheritance, and impacts children regarding legal status and identity registration. In conclusion, there is a need for synergy between religious law and state law to provide comprehensive legal protection. Marriage registration should be understood as both a mandate of Shari'ah and a constitutional obligation to achieve justice and the welfare of the family.